Assessing the Impact of Supply Chain Management on Competitive Advantage and Operational Performance: A Case of Four Star Hotels of Mauritius - Vencataya, Lomendra; Seebaluck, Ashley Keshwar; Doorga, Deveshika (International Review of Management and Marketing, 2016)
operational performance with reference to the four star hotels of Mauritius. A questionnaire was designed and administered to the managers of the four star hotels of Mauritius. The main conclusion of this study corresponds to those of previous studies which show that SCM does have an impact on competitive advantage and operational performance. For instance, this study demonstrates that effective SCM practices can lead to better management of the supply chain which in turn can have a significant impact on competitive advantage of the hotels. Therefore, effective supply chain management practices should substantially enhance the competitive advantage and operational performance of four star hotels in Mauritius. This study would be of relevance to other hotels which are implementing a system for managing their supply chains. The practice of supply chain management could provide an avenue for enhancing the competitiveness of the hotel sector of Mauritius. Keywords: Supply Chain Management, Operational Performance, Competitive Advantage JEL Classifications: C44, R41